2022
DOI: 10.1039/d2dt03657f
|View full text |Cite
|
Sign up to set email alerts
|

Mapping boron catalysis onto a phosphorus cluster platform

Abstract: Clusters of main group elements, such as phosphorus, arsenic, germanium, and tin - called Zintl clusters - have been known for more than a century. However, their application in main...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…17,18 Recently, we have found that boron-functionalized [P 7 ] cages can be applied as transition-metal free catalysts in hydroboration reactions. 19,20 Heteroallene insertion between labile non-cluster tetrelpnictogen bonds has previously been reported. [21][22][23][24][25][26] In 2022 we found for the first time this reactivity with Zintl-derived clusters.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…17,18 Recently, we have found that boron-functionalized [P 7 ] cages can be applied as transition-metal free catalysts in hydroboration reactions. 19,20 Heteroallene insertion between labile non-cluster tetrelpnictogen bonds has previously been reported. [21][22][23][24][25][26] In 2022 we found for the first time this reactivity with Zintl-derived clusters.…”
Section: Introductionmentioning
confidence: 94%
“…17,18 Recently, we have found that boron-functionalized [P 7 ] cages can be applied as transition-metal free catalysts in hydroboration reactions. 19,20…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that boranes can be tethered using aliphatic linkers onto the [P 7 ] cluster and then exploited in Lewis acid catalysis while the cluster remains an innocent platform. 33 We have found that in the case of catalyst ([(BBN)P 7 ] 2− ([ 1 ] 2− ); BBN = 9-borabicyclo[3.3.1]nonane), where the boron is directly coordinated to [P 7 ], the reduction of carbonyls and CO 2 could be mediated with high efficiency compared to other metal-free catalysts. 34 Mechanistic studies revealed that the [P 7 ] cluster is non-innocent and substrate activation happens between both the boron and phosphorus centres in a cooperative fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic carbodiimide hydroboration reactions were first reported in 2016 using magnesium catalysts. [8,9] Since then, catalysts for carbodiimide hydroboration using pinacolborane (HBpin) have been reported from across the periodic table, including transition metal, [10][11][12] main group, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and actinide [28] catalysts. Most carbodiimide hydroboration catalysts operate at elevated temperatures (50-80 °C).…”
Section: Introductionmentioning
confidence: 99%
“…Most carbodiimide hydroboration catalysts operate at elevated temperatures (50-80 °C). [8][9][10][16][17][18][19][20][21][22][23][24]27,28] Exceptions that operate at room temperature include a carbatrane magnesium hydride complex, [14] the 9-borabicyclo[3.3.1]nonane dimer, [15] manganese(II) bis(hexamethyldisilazide), [11] a boron-functionalized heptaphosphide Zintl cluster, [25] 9,10-dihydro-9,10-diboraanthracene dianions, [26] and an N-heterocyclic carbene-supported copper alkoxide complex. [12] Initial studies of catalytic isocyanate hydroboration reactions in 2016 and 2017 reported magnesium catalysts for the dihydroboration of isocyanates to form N,O-bis(boryl) hemiaminal products or hydrodeoxygenation reactions to generate N-methyl amines.…”
Section: Introductionmentioning
confidence: 99%